Perilaku Pencarian Informasi Kesehatan pada Masyarakat di Kelurahan Bukit Apit Puhun Kota Bukittinggi - Addin, Puti Aliya; Nelisa, Malta (Scinary, 2023)
The aim of this research is to describe (1) the health information seeking behavior of the community in Bukit Apit Puhun Village, Bukittinggi City at the initiation stage, (2) the health information seeking behavior of the community in Bukit Apit Puhun Village, Bukittinggi City at the selection stage. ), (3) health information seeking behavior among the community in Bukit Apit Puhun Village, Bukittinggi City at the exploration stage. This research uses quantitative research with descriptive methods. The population in this study was the community in Bukit Apit Puhun Village, Bukittinggi City, with samples taken using simple random sampling. The main instrument used was a research questionnaire which had been tested for validity and reliability, the sample size was 97 people. The variables in this research are the people in Bukit Apit Puhun Village, Bukittinggi City. Data collection techniques are questionnaire techniques and questionnaire data processing through editing and tabulation stages. The results of the research are: (1) health information seeking behavior at the initiation stage has a total average score of 3.17 and is on an interval scale of 2.50 – 3.24 (good). At this initiation stage, respondents tend to be more influenced by the demographic or socio-cultural conditions of the community where they live. This factor helps in understanding how the various aspects of human life are composed; (2) health information seeking behavior at the selection stage has a total average score of 3.14 and is on an interval scale of 2.50 – 3.24 (good). At this selection stage, respondents tend to collect information they obtain through social media. Collecting health information intelligently and critically is very useful in making wise decisions; (3) health information seeking behavior at the exploration stage has a total average score of 3.06 and is on an interval scale of 2.50 – 3.24 (good). At this exploration stage, respondents' health information needs are met through the initiation, selection and exploration stages. Fulfilling the need for health information can be an effort to maintain and improve the health of individuals and society. Overall, the results of the research analysis can be concluded by researchers that the public's health information seeking behavior is in good condition.